2020
DOI: 10.1145/3411829
|View full text |Cite
|
Sign up to set email alerts
|

Designing Interactions Beyond Conscious Control

Abstract: Recent research in psychology distinguishes levels of consciousness into a tripartite model-conscious, unconscious and metaconscious. HCI technologies largely focus on the conscious pathway for computer-to-human interaction, requiring explicit user attention and action. In contrast, the other two pathways provide opportunities to create new interfaces that can alter emotion, cognition and behavior without demands on attentional resources. These direct interfaces connect to cognitive processes that are in our p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 77 publications
1
6
0
Order By: Relevance
“…For example when we feel sad while watching movies or listening to music, we can clearly perceive that our body is responding with difficult breathing, feeling a lump in the throat, or crying, etc. Jain et al [6] proposed some body responses are always hidden to the perception that they are so subliminal that we could not even notice the changing, for example when we are watching movies we can't tell how our glucose levels are changing.…”
Section: Mind To Body Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…For example when we feel sad while watching movies or listening to music, we can clearly perceive that our body is responding with difficult breathing, feeling a lump in the throat, or crying, etc. Jain et al [6] proposed some body responses are always hidden to the perception that they are so subliminal that we could not even notice the changing, for example when we are watching movies we can't tell how our glucose levels are changing.…”
Section: Mind To Body Modelmentioning
confidence: 99%
“…This question from James-Lange theory of emotion [23] about the expression and experience of emotion can be regarded as that phenomenon of an body action could also evoke the associated emotion. Jain et al [6] proposed that interoceptive technologies means inducing emotions from the body to mind. For example, the project from Fukushima et al [24] showed that moving the muscles on the face to generate a smile may lead to the emotion of happiness in the mind.…”
Section: Interoception Interaction and Body To Mind Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…We aim to augment the aesthetic experience through enhancing the capability of feeling frisson which is usually affected by music appreciation and training [16], personality [50], openness [13], physiological and neural features [42]. While it may not be possible to change these individual characteristics directly, we aim to mediate frisson between people using a thermohaptic approach that allows neighboring people to perceive frisson beyond their conscious control [24]. For example, if a person who is sensitive to music and appreciates music feels frisson at a specific moment in a piece, a person who receives our actuation might also feel this frisson or at the very least have their attention drawn to how special that moment is.…”
Section: Introductionmentioning
confidence: 99%